A moderação da concentração setorial no efeito do ambiente institucional na performance empresarial - Kallás, David (2014)
This research extend the understanding of firm performance by proposing that industry conditions, specifically industry concentration, moderates the relation among institutions and firm performance. It is already known that institution matters (Makino et al., 2004) and that promarket reforms positively affect firms’ profitability in developing countries for both domestic and foreign firms (Cuervo-Cazurra & Dau, 2009). The explanation is based on transaction costs economics (Coase, 1937; Commons, 1934). However, it is not known whether this effect is the same for all industries and if there is any moderating effect. This thesis built a database of 230,222 observations of 10,903 companies in 64 countries in a 23 years interval. Data was gathered from various sources. Regressions tested the interaction between the Herfindahl-Hirschman Index (HHI) and six institutional variables, considering three dependent variables: return on assets (ROA), return on equity (ROE) and 3-year compound annual sales growth rate. Two empirical strategies were used: fixed effects and hierarchical (multilevel) models. Results confirmed the hypothesis and were significant for the negative interaction between HHI and four institutional variables: voice and accountability, govern effectiveness, regulatory quality and control of corruption. Industry concentration moderates the effect of institutions on firm performance. When institutions are strong, the strength of stakeholders like unions, associations, press and consumers became bargaining power, limiting firms power and opportunism. Legal rules and institutions, common law and others, limit unilateral power in contractual relations of al kinds, whatever may be its source (Macneil, 1980). In addition, this thesis proposes that the protection against opportunism is mainly on informal institutions, like democracy protection, consumer rights and control of corruption. Strong institutions enforce contractual commitments, in particular, social contracts (Argyres & Liebeskind, 1999). As a result, this thesis argues that strategies of expansion within the industry, as market share dominance, mergers and acquisitions and growth strategies may fit better on weak institutional contexts. Firms that have high market share must acknowledge the negative impact of institutional improvements. Finally, governs must understand that industries and firms benefit unequally from institutional changes. Anticipating this knowledge may drive the formulation of efficient and fair public policies. The main limitations are the database was exclusively made of public traded companies, problems on industry classification for diversified firms, and that this work did not directly investigate the bargaining power or opportunism, but the moderating effect of industry concentration.